Is the presence of mosquitoes an indicator of poor environmental sanitation?. (1st March 2023) - Olagunju, Emmanuel Ajibola
Abstract: The World Health Organization has designated mosquitoes as the most lethal animal since they are known to spread pathogen-transmitting organisms. Understanding the many environmental elements that contribute to the spread of these vectors is one of the many strategies used to stop them. If there are mosquitoes around people, it may indicate that there is not an appropriate environmental sanitation program in place in the community or region. Environmental sanitation involves improving any elements of the physical environment that could have a negative impact on a person's survival, health, or physical environment. Keywords containing ' Aedes, ' ' Culex, ' 'Anopheles, ' 'dengue, ' 'malaria, ' 'yellow fever, ' 'Zika, ' 'West Nile, ' 'chikungunya, ' 'resident, ' 'environment, ' 'sanitation, ' 'mosquito control, ' and 'breeding sites' of published articles on PubMed, Google Scholar, and ResearchGate were reviewed. It was discovered that the general population should be involved in mosquito and mosquito-borne disease control. Collaboration between health professionals and the general population is essential. The purpose of this paper is to increase public awareness of environmental health issues related to diseases carried by mosquitoes. HIGHLIGHTS: Effect of environmental sanitation on the spread of mosquitoes This study makes recommendations for collaboration between health workers and the public. It enhances the need for proper sanitation. It creates awareness for the general public. Graphical Abstract